Physical and Mechanical Properties of Fraxinus Spp. (Ash) from Some Localities - Shukla, N. K. (Indian Forester, 1983)
Based on tbe tests conducted on small clear specimens, the physical and mechanical properties of Fraxinus micrantha (Nainital, U.P.), F. hookeri (Chamba, HP), F. xanthoxyloides (Kulu, HP) and F. spp. (Srinagar, J & K) are reported and discussed. The test results have been compared with foreign ash i.e. F. excelsior (UK) and F. americana (USA as well as Canada). The comparative suitability indices for various end-uses have also been evaluated for Indian and Foreign ash from the basic strength data and reported. From the data of Indian ash collected so far, it is concluded that while the Indian ash is slightly heavier than foreign ash, in strength properties there is no notworthy difference between the two. Some end-uses are also suggested.